2019
DOI: 10.3389/fphar.2019.01116
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Selected MET and EGFR Inhibitors Decreases Melanoma Cells’ Invasive Abilities

Abstract: We have previously shown that combination of foretinib, an inhibitor of MET (hepatocyte growth factor receptor), with gefitinib or lapatinib, inhibitors of EGFR (epidermal growth factor receptor), has a synergistic cytotoxic effect on melanoma cells. However, there are cancer cells resistant to drugs’ treatment which are still able to invade. Thus, in this study, we examined the influence of these drugs on invasive abilities of melanoma cells. To investigate cell migration and invasion, Transwell inserts and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…As we have previously shown, EGFR and MET seem to be promising targets for anti-melanoma combination therapy using small molecule inhibitors. Foretinib (F, MET inhibitor) and lapatinib (L, EGFR inhibitor) used simultaneously were able to synergistically decrease the viability of melanoma cells, and also significantly diminish the invasive abilities and proteolytic activity of these cells [10,11]. Here, we have demonstrated that resistant cells exhibit overexpression of both studied receptors, which also corresponds to the elevated rate of migration and invasion.…”
Section: The Sensitivity Of Resistant Cells To Egfr and Met Inhibitorsmentioning
confidence: 67%
See 2 more Smart Citations
“…As we have previously shown, EGFR and MET seem to be promising targets for anti-melanoma combination therapy using small molecule inhibitors. Foretinib (F, MET inhibitor) and lapatinib (L, EGFR inhibitor) used simultaneously were able to synergistically decrease the viability of melanoma cells, and also significantly diminish the invasive abilities and proteolytic activity of these cells [10,11]. Here, we have demonstrated that resistant cells exhibit overexpression of both studied receptors, which also corresponds to the elevated rate of migration and invasion.…”
Section: The Sensitivity Of Resistant Cells To Egfr and Met Inhibitorsmentioning
confidence: 67%
“…Taking into account the overexpression and increased activation of RTKs in generated resistant cells, priming these molecules as potential therapy targets, we tested the efficiency of combination treatment using inhibitors of EGFR (lapatinib) and MET (foretinib) in this model. In our previous work, we have already demonstrated that dual inhibition of EGFR/MET was able to elicit a synergistic cytotoxic effect in melanoma cell lines, accompanied by a decrease in their invasive abilities [10,11]. Herein, we analyzed the effectiveness of a proposed therapy in A375 and WM9 cell lines resistant to vemurafenib, and noticed that both models demonstrate similar responsiveness to RTKs inhibitors compared with parental lines in terms of reduction of viability.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In our previous studies, we demonstrated that the WM1341D cell line exhibits lower invasive abilities than A375, WM9, and Hs294T cell lines [ 37 , 38 ]. Compared to other cells, WM1341D formed a lower number of invadopodia (adhesive structures with proteolytic activity), which are utilized by cancer cells to digest the extracellular matrix and invade tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The smallest number of digesting cells as well as the lowest digestion area were observed in WM1341D cells. A375 and Hs294T cells digested to a greater extent than WM1341D [ 37 , 38 ]. Our current results indicate that the invasiveness of the examined melanoma cells correlated positively with the level of PARP1 in these cells.…”
Section: Discussionmentioning
confidence: 99%